Concentration of Plasmodium falciparum gametocytes in whole blood samples by magnetic cell sorting enhances parasite infection rates in mosquito feeding assays - Isaie J. Reuling; Will J. R. Stone; Marga van de Vegte-Bolmer; Geert-Jan van Gemert; Rianne Siebelink-Stoter; Wouter Graumans; Kjerstin Lanke; Teun Bousema; Robert W. Sauerwein (Malaria Journal, 2017)
Abstract Background Mosquito-feeding assays are important tools to guide the development and support the evaluation of transmission-blocking interventions. These functional bioassays measure the sporogonic development of gametocytes in blood-fed mosquitoes. Measuring the infectivity of low gametocyte densities has become increasingly important in malaria elimination scenarios. This will pose challenges to the sensitivity and throughput of existing mosquito-feeding assay protocols. Here, different gametocyte concentration methods of blood samples were explored to optimize conditions for detection of positive mosquito infections. Methods Mature gametocytes of Plasmodium falciparum were diluted into whole blood samples of malaria-naïve volunteers. Standard centrifugation, Percoll gradient, magnetic cell sorting (MACS) enrichment were compared using starting blood volumes larger than the control (direct) feed. Results MACS gametocyte enrichment resulted in the highest infection intensity with statistically significant increases in mean oocyst density in 2 of 3 experiments (p = 0.0003; p ≤ 0.0001; p = 0.2348). The Percoll gradient and standard centrifugation procedures resulted in variable infectivity. A significant increase in the proportion of infected mosquitoes and oocyst density was found when larger volumes of gametocyte-infected blood were used with the MACS procedure. Conclusions The current study demonstrates that concentration methods of P. falciparum gametocyte-infected whole blood samples can enhance transmission in mosquito-feeding assays. Gametocyte purification by MACS was the most efficient method, allowing the assessment of gametocyte infectivity in low-density gametocyte infections, as can be expected in natural or experimental conditions.